Hedges in Interfaith Discourse: A Case Study of Indonesian Religious Figures in A Podcast Dialogue - Dian Budiarti; Rizki Erdayani (Masyarakat Linguistik Indonesia, 2026)
This study investigates the use of hedges in an interfaith podcast dialogue featuring six religious figures representing Indonesia’s officially recognized religions. Specifically, it examines the types and functions of hedging in spoken religious discourse using data collected from an episode of the LOGIN podcast. All utterances containing hedging devices were identified and categorized into structural types, and their pragmatic roles were analyzed through qualitative descriptive methods grounded in pragmatic theory. The findings reveal that there are three major types of hedges that are actively used to manage interpersonal dynamics and negotiate meaning in a pluralistic context. Shields were the most frequent type (38.89%), followed by attribution markers (33.33%) and approximators (27.78%). Functionally, hedges performed epistemic, affective, and discourse-management role, which allow speakers to express uncertainty, soften claims, and maintain dialogic openness. These strategies helped speakers express their convictions while respecting differing beliefs for fostering mutual understanding. It is expected that this study contributes to the understanding of how hedging operates in religiously diverse, media-mediated interactions, and highlights its pragmatic value in maintaining a tolerant interfaith dialogue.